Effect of long term oxygen treatment at home in children with pulmonary vascular disease. Issue 4 (April 1986) - Bowyer, J J; Busst, C M; Denison, D M; Shinebourne, E A
Abstract : Inhalation of 100% oxygen by nine children with pulmonary vascular disease increased pulmonary blood flow measured at cardiac catheterisation; there was no significant change in pulmonary artery pressure. Fifteen children with pulmonary vascular disease that was severe enough to preclude corrective cardiac operation were studied to determine the effect of long term oxygen treatment on pulmonary vascular disease. Nine received long term domiciliary oxygen for a minimum of twelve hours a day for up to five years. Though the untreated group closely resembled the treated group their survival was significantly less good. All nine treated children are alive whereas five of the six children who did not receive oxygen have died.